Trinidad Hilton - (:unkn) unknown (Brown Knight and Truscott Ltd., 2010)
Description printed on the back of the postcard:"The Caribbean's newest luxury hotel overlooking Port-of-Spain …restaurants, bars, pools, gardens, shops, each room has its own private balcony..completely air conditioned." This postcard is addressed to Frank and Doris Gary of New Jersey, United States of America and affixed to the card is a 12 cents Trinidad and Tobago postage stamp."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hotels; 1969